Purtscher’s retinopathy: a case report - Chaudhary, Sushma; Gupta, Sharad; Yadav, Reena; Kabmle, Vinit Kumar; Shrestha, Satbodh (Journal of Chitwan Medical College, 2020)
Purtscher’s retinopathy is a rare haemorrhagic and vaso-occlusive vasculopathy following severe head trauma associated with sudden blindness. Here we report a case of 28 years old male presented to out-patient department with history of sudden and painless loss of vision in his right eye for two days. He gave history of head injury following bike accident. At the time of presentation his best corrected visual acuity was 1/60 in the right eye and 6/6 in the left eye. On examination, anterior segments of both eyes were normal. On fundus examination, right eye revealed retinal whitening in the peripapillary region (Purtscher’s flecken), an intraretinal hemorrhage and signs of macular edema whereas left eye was unremarkable. Findings were suggestive of right eye purtscher’s retinopathy. Optical coherence tomography and fundus fluorescence angiography was done to support the diagnosis. Purtscher’s retinopathy should not be neglected because it is associated with different systemic disease. Its pathophysiology remains unclear and there is no definite treatment but meticulous management is urgent to prevent from severe complications.